'Caterpillars and Catalysts': A Year of Literacy Learning in an Early Years Classroom Privileging Dramatic Pedagogies. Issue 3 (September 2016) - Harden, Annette
'CATERPILLARS AND CATALYSTS' follows the journey into literacy of one of four young children whose case studies formed a major part of a PhD research study. Using the metaphor of the hungry caterpillar, the author traces the effect on writing development of a pedagogy privileging drama and puppetry, supported by explicit phonics teaching. The context was a Queensland school in the inaugural year of Preparatory schooling, 2007. The findings of the study, in relation to children's development, included a strong motivation and persistence in writing within dramatic play and real-life contexts, as well as a sense of agency as capable writers. The implications of the research were that dramatic pedagogies may assist teachers to provide an authentic and balanced approach to introducing the alphabetic symbol system, giving it meaning and relevance in young children's lives.ood education and care (ECEC) it is understood in